Unforeseen Hodgkin Lymphoma Hidden behind Hypercalcemia. (18th November 2019) - Ghrewati, Moutaz; Singh, Balraj; Kaur, Parminder; Maroules, Michael
Abstract : As one of the leading causes of hypercalcemia, malignancy is an essential consideration when patients present with such symptomology. While certain tumors are more known to cause hypercalcemia, it can occur with almost any type of cancer. Hodgkin lymphoma is an infrequent cause of hypercalcemia. Only a few case reports have been published in the literature to date. We report an unusual case of a 61-year-old female who presented with altered mental status, nausea, vomiting, and dizziness and was found to have multiple enlarged lymph nodes, and blood work showed hypercalcemia. Biopsy of the cervical lymph node showed Hodgkin lymphoma of the nodular sclerosis subtype. Our case aims to raise awareness of this rare but significant presentation of hypercalcemia and how timely treatment of calcium levels can facilitate the employment of available chemotherapeutic options.